Validating the Swedish STOP-D: a brief tool for depression, anxiety, stress, anger and social support - Larsson, Andreas; Milos Nymberg, Veronica; Nymberg, Peter; Sundström, Felicia T. A. (Frontiers in Psychology, 2026)
Psychological distress, including depression, anxiety, and stress, requires time-efficient assessment tools suited for digital and momentary settings. The Screening Tool for Psychological Distress (STOP-D) is a five-item scale developed for brief mental health screening, but it has not yet been validated in Swedish. This study aimed to evaluate the psychometric properties and diagnostic accuracy of the Swedish STOP-D in a non-clinical adult sample. A total of 427 Swedish-speaking adults (mean age = 49.42, SD = 16.34 years) completed the STOP-D, the Patient Health Questionnaire-4 (PHQ-4), the Single-Item Stress Scale (SISE), and the Need Satisfaction and Frustration Scale (NSFS). ROC analyses were conducted using PHQ-2 and GAD-2 (cut-off ≥ 3) and the SISE (cut-off ≥ 6 and 7). Feature importance was examined using the Boruta algorithm. Exploratory Graph Analysis (EGA) assessed the internal structure. The STOP-D items for Sadness and Anxiety showed excellent classification accuracy for depression and anxiety (AUC = 0.87–0.89). Stress showed lower accuracy (AUC = 0.65–0.67). EGA supported a two-factor model, with STOP-D items for Sad, Anxiety and Stress clustering separately from Anger and Lack of Social Support. The Swedish STOP-D is a valid brief tool for assessing core psychological distress. Items for anger and social support may add clinical value and represent distinct processes relevant for future individualized and ecological assessment.